Mango Pectic Oligosaccharides: A Novel Prebiotic for Functional Food - Wongkaew, Malaiporn; Tangjaidee, Pipat; Leksawasdi, Noppol; Jantanasakulwong, Kittisak; Rachtanapun, Pornchai; Seesuriyachan, Phisit; Phimolsiripol, Yuthana; Chaiyaso, Thanongsak; Ruksiriwanich, Warintorn; Jantrawut, Pensak; Sommano, Sarana Rose (Frontiers in Nutrition, 2022)
Prebiotics are functional food ingredients that assist probiotic growth and render many other health benefits. Mango peel is the biomass of the processing industry and recently value added as dietary fibre pectin. Besides, its general use as food additive, mango peel pectin (MPP) is partially hydrolysed by pectinase to obtain pectic-oligosaccharides [1] that recently gained attention as novel prebiotic products and in the medical research. This review describes probiotic candidates responsible for the digestion of pectin derivatives and the advantages of pectic-oligosaccharides as functional additives and their current best retrieving options. Mango pectic-oligosaccharide [1] recovery from low methoxyl MPP from mango with the prebiotic performance both in-vivo and in-vitro environments are discussed. Current research gaps and the potential developments in the field are also explored. The overall worthiness of this article is the potential use of the cheap-green food processing bioresource for high value component.